2018
DOI: 10.6007/ijarbss/v8-i10/4753
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Marketing in Entrepreneurial Development and Poverty Alleviation in Nigeria

Abstract: Various governments all over the world have acknowledged that entrepreneurship and the formation of micro, small and medium enterprises is the key to economic growth, employment generation and poverty alleviation. However, for entrepreneurship to play this role effectively and efficiently, it must be a vital and an integral component of productivity and growth. Most SMEs in Nigeria experience abysmally low performance, and some even fold up within five years of start-up despite governmental efforts in encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Several previous studies have shown how important marketing is for small businesses because if an entrepreneur has all the necessary management skills, without marketing knowledge and skills, an entrepreneur may not be successful in business. Oparah et al (2018) show that marketing is one of the critical factors that can determine the success or failure of any new venture. This suggests that the acquisition of marketing skills by business owners or managers is expected to improve the performance of MSMEs.…”
Section: The Effects Of Owner or Managers' Management Skills On The P...mentioning
confidence: 99%
“…Several previous studies have shown how important marketing is for small businesses because if an entrepreneur has all the necessary management skills, without marketing knowledge and skills, an entrepreneur may not be successful in business. Oparah et al (2018) show that marketing is one of the critical factors that can determine the success or failure of any new venture. This suggests that the acquisition of marketing skills by business owners or managers is expected to improve the performance of MSMEs.…”
Section: The Effects Of Owner or Managers' Management Skills On The P...mentioning
confidence: 99%